Governance for Structural Transformation in Africa - Elhiraika, Adam B.; Ibrahim, Gamal; Davis, William (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
XX, 317 p. 45 illus., 32 illus. in color.